The TRAPs From Microglial Vesicles Protect Against Listeria Infection in the CNS - Wang, Chao; Wang, Yang; Shi, Xiaochen; Tang, Xudong; Cheng, Wei; Wang, Xueyan; An, Yanan; Li, Shulin; Xu, Hongyue; Li, Yan; Luan, Wenjing; Wang, Xuefei; et al. (Frontiers in Cellular Neuroscience, 2019)
Previous studies have demonstrated that T cells and microglia could fight against cerebral Listeria monocytogenes (Listeria); however, their synergistic anti-Listeria mechanisms remain unknown. Following Listeria infection in a culture system, we found that microglia, but not nerve cells, could release extracellular traps (ETs) which originated from microglial vesicles. Specific inhibitor analysis showed that extracellular DNA (eDNA), matrix metallopeptidases (MMP9 and MMP12), citrullinated histone H3, and peptidyl arginine deiminase 2 were the major components of microglial ETs (MiETs) and were also the components of vesicles. Systematic analysis indicated that Listeria-induced MiETs were cytosolic reactive oxygen species (ROS)- and NADPH oxidase (NOX)-dependent and involved ERK. MiETs were exhibited in Listeria-infected mouse brain and protected against Listeria infection via bacterial killing in a mouse meningitis model, and MiETs existed in cerebrospinal fluid (CSF) from Listeria meningitis patients in vivo and in vitro. Additionally, interferon-γ could induce MiET formation in Listeria-infected microglia in vitro that was mediated by NOX, and there was a positive relationship between the elevated level of IFN-γ and eDNA and nucleosomes in the brain homogenates and CSF of Listeria meningitis model mice and in the CSF before treatment in clinical Listeria meningitis patients. Together, this is the first report of MiET formation, these findings pave the way for deeper exploration of the innate immune response to pathogens in CNS.